Reproductive health needs and sexual practices of female adolescents with perinatally acquired HIV - Mkandawire, Beatrice Masozi (2021)
The advent of Anti-retrovirals (ARV), a life longing drug, has enabled more and more children with perinatally acquired Human Immunodeficiency Virus (HIV) to reach adolescence, a situation which was not anticipated. These adolescents are at a stage where they are making transition from childhood and are undergoing physical and emotional changes and begin sexual exploration hence are vulnerable to HIV re-infection and other sexual infections. However, to date, this group has received relatively less attention in the field of reproductive health care as most of such services are adult centered. The aim of the study was to explore reproductive health needs and sexual practices of female adolescents with perinatally acquired HIV. An exploratory study utilizing qualitative approach was conducted at Baylor College of Medicine-Lilongwe District, Malawi. A total of ten female adolescents with perinatally acquired HIV, aged between 18-19 years were purposively selected and interviewed using a semi structured interview guide. All the interviews were audio taped and transcribed verbatim. Thematic Analysis (TA) was used to analyze data manually. The study findings have shown that access to comprehensive health information and services remains a challenge. Participants expressed ignorance on other reproductive options available and how to use them. The study revealed that the desire to have children in future was common amongst participants. Participants showed understanding of contraception. However, there seemed to be a huge gap between their knowledge of different types of contraception and access to these services. The study demonstrated that the commonly used contraception was injectable form, due to the secrecy surrounding it. It was noted that participants were sexually active. However, they were not using dual protection methods of contraception despite their HIV sero status. ALHIV need more information, skills, and support to practice healthy behaviours. Tailored interventions are required for adolescents living with HIV to improve their sexual and reproductive health.